Countries starting lifting restrictions on exercise and sport under Covid-19 lockdowns: How do they compare? - Payne,R.; Malyshkina, M (2020)
Governments around Europe and other parts of the world lifting restrictions on exercise and sport under the Covid-19 lockdowns. ISCA puts the spotlight on the status of physical activity and sport across Europe and beyond in this exclusive mapping by country. ISCA presents the current status of physical activity and sport under Covid-19 lockdowns in 56 countries and counting (including 39 European countries)